GluN3A subunit tunes NMDA receptor synaptic trafficking and content during postnatal brain development - Inmaculada M. González-González; John A. Gray; Joana Ferreira; María Jose Conde-Dusman; Delphine Bouchet; Isabel Perez-Otaño; Laurent Groc (Cell Reports, 2023)
Summary: Signaling via N-methyl-d-aspartate receptors (NMDARs) is critical for the maturation of glutamatergic synapses, partly through a developmental switch from immature synapses expressing primarily GluN2B- and GluN3A-containing subtypes to GluN2A-rich mature ones. This subunit switch is thought to underlie the synaptic stabilization of NMDARs necessary for neural network consolidation. However, the cellular mechanisms controlling the NMDAR exchange remain unclear. Using a combination of single-molecule and confocal imaging and biochemical and electrophysiological approaches, we show that surface GluN3A-NMDARs form a highly diffusive receptor pool that is loosely anchored to synapses. Remarkably, changes in GluN3A subunit expression selectively alter the surface diffusion and synaptic anchoring of GluN2A- but not GluN2B-NMDARs, possibly through altered interactions with cell surface receptors. The effects of GluN3A on NMDAR surface diffusion are restricted to an early time window of postnatal development in rodents, allowing GluN3A subunits to control the timing of NMDAR signaling maturation and neuronal network refinements.